2004
DOI: 10.1007/978-3-540-24659-6_20
|View full text |Cite
|
Sign up to set email alerts
|

Effort Estimation Based on Collaborative Filtering

Abstract: Effort estimation methods are one of the important tools for project managers in controlling human resources of ongoing or future software projects. The estimations require historical project data including process and product metrics that characterize past projects. Practically, in using the estimation methods, it is a problem that the historical project data frequently contain substantial missing values. In this paper, we propose an effort estimation method based on Collaborative Filtering for solving the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The estimation accuracy of SDEE models depends on data sets and their properties. 3,24,29,30,35,40,43 During our study, we found that some of the data sets collected from industry are being frequently used by researchers; of course, the availability is the prominent reason of it. Some of the researchers have also used pilot studies or even student projects to build and assess their models such as in previous studies.…”
Section: Data Setsmentioning
confidence: 84%
See 3 more Smart Citations
“…The estimation accuracy of SDEE models depends on data sets and their properties. 3,24,29,30,35,40,43 During our study, we found that some of the data sets collected from industry are being frequently used by researchers; of course, the availability is the prominent reason of it. Some of the researchers have also used pilot studies or even student projects to build and assess their models such as in previous studies.…”
Section: Data Setsmentioning
confidence: 84%
“…Data sets are the key ingredients to any SDEE model; after all, an SDEE model is nothing but the finest generalized approximation of the past experiences of previously completed projects so that it can be used for the estimation of new software. The estimation accuracy of SDEE models depends on data sets and their properties . During our study, we found that some of the data sets collected from industry are being frequently used by researchers; of course, the availability is the prominent reason of it.…”
Section: Data Setsmentioning
confidence: 85%
See 2 more Smart Citations
“…Using collaborative filtering technology with in-process measurements of the target project and a database of over 1000 past projects benchmark data, project estimates and predictions were made. Collaborative filtering is one of the estimation techniques using defective data having substantial missing values, in information retrieval research domain [4]. 3) Using the automatic measurement platform named "Empirical Project Monitor (EPM)," the program modification history from the configuration management system, faults and maintenance data from the bug tracking system, and project e-mail information from the mailing list management system were analyzed.…”
Section: The In-process Project Measurement Model Based On Previous Ementioning
confidence: 99%